L'héritage du Che : un point de vue antillais - Pierre-Charles, Philippe; Habel, Janette (Montreuil-sous-Bois: Tranchées, 1997)
"Philippe Pierre-Charles ; préface Janette Habel Bibliotheek François Vercammen"